We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
99
4
avatar

Evaluate the sum \(\dfrac{6}{3^2-1}+\dfrac{6}{5^2-1}+\dfrac{6}{7^2-1}+\dfrac{6}{9^2-1}+\cdots.\)

 Jun 26, 2019
 #1
avatar
0

As n grows toward infinity, the 1/n+1 vanishes to 0, so the sum of the infinite series is 3/2

 Jun 26, 2019
 #2
avatar
0

sumfor(n, 1, 1000000, 6 / ((2*n + 1)^2 - 1)) = 3 / 2

 Jun 26, 2019
 #3
avatar+103122 
+2

6  [     1 / [ 3^2 - 1 ]   +   1 / [ 5^2 - 1]   +  1/[7^2  - 1] +   1/ [ 9^2 - 1 ] +....... ]   =

 

6 [     1 /  8    +   1 / 24    +     1/48  +  1/80  +   ..... ]    =

 

6  [   1 / [ 2*4]   +  1/ [ 4*6]  +  1/[ 6*8] + 1/ [8*10] +  ....... ]   =

 

6   [ (1/4) ]  [   1 / [1 * 2]   +  1/ [2 *3]   + 1/ [ 3*4]  + 1 / [ 4*5] +   .....]

 

Note that            1/ [ n * (n + 1) ]   =         1 / n   -  1/[ n + 1]

 

So we can write

 

(6/4)   [   ( 1/1 - 1/2) + (1/2 - 1/3)  + (1/3 - 1/4) + (1/4 - 1/5)  + .......] =

 

(3/2)  [   1   + ( 1/2 -1/2) + (1/3 - 1/3)   + (1/4 - 1/4)  + ........ +  (-1/n) ]  = 

 

(3/2) [ 1  -   1/n ]         as n ⇒  infinity,   1/n   ⇒   0

 

So we have

 

(3/2 )  [ 1 - 0]  =

 

(3/2) (1)   =

 

3/2

 

 

cool cool cool

 Jun 26, 2019
 #4
avatar+8724 
+4

\(S\quad{=\quad}\dfrac{6}{3^2-1}+\dfrac{6}{5^2-1}+\dfrac{6}{7^2-1}+\dfrac{6}{9^2-1}+\cdots\\~\\~\\ S_m\quad{=\quad}\sum\limits_{n=1}^{m}\ \dfrac{6}{(2n+1)^2-1}\\~\\~\\ S_m\quad{=\quad}\sum\limits_{n=1}^{m}\ \dfrac{6}{4n^2+4n}\\~\\~\\ S_m\quad{=\quad}\sum\limits_{n=1}^{m}\ \dfrac{6}{4n(n+1)}\\~\\~\\ S_m\quad{=\quad}\sum\limits_{n=1}^{m}\ \dfrac32\bigg(\dfrac{1}{n(n+1)}\bigg)\\~\\~\\ S_m\quad{=\quad}\sum\limits_{n=1}^{m}\ \dfrac32\bigg(\dfrac{1}{n}-\dfrac{1}{n+1}\bigg)\\~\\~\\ S_m\quad{=\quad}\dfrac32\bigg(\dfrac{1}{1}-\dfrac{1}{2}+\dfrac{1}{2}-\dfrac{1}{3}+\dfrac{1}{3}- \dfrac{1}{4}+\dots+\dfrac{1}{m-1}-\dfrac{1}{m}+\dfrac{1}{m}-\dfrac{1}{m+1}\bigg)\\~\\~\\ S_m\quad{=\quad}\dfrac32\bigg(\dfrac11-\dfrac1{m+1}\bigg)\\~\\~\\ S_m\quad{=\quad}\dfrac32\bigg(1-\dfrac1{m+1}\bigg)\\~\\~\\ S\quad=\quad\lim\limits_{m\rightarrow\infty}S_m\\~\\~\\ S\quad=\quad\lim\limits_{m\rightarrow\infty}\dfrac32\bigg(1-\dfrac1{m+1}\bigg)\\~\\~\\ S\quad=\quad\dfrac32\bigg(1-0\bigg)\\~\\~\\ S\quad=\quad\dfrac32\)_

 Jun 26, 2019

5 Online Users